Utilização do processo foto-Fenton induzido com ferrioxalato no tratamento de efluentes têxteis - Souza, Patrícia Simôes Carraro (2016)
This paper presents the study of the removal of pollutants from a textile effluent using the photo-Fenton reaction induced with ferrioxalate. The reactions were performed in a batch system in beakers under magnetic stirrer, set in a chamber with an inner lining of stainless steel, equipped with mercury vapor lamps without the original bulb. The textile effluent from the dyeing step of knitted cotton was collected in a dyeing plant located in the northwestern region of Paraná. The main dyes present were Procion Blue HEGN and Procion Red HE7B. The characterization of the textile effluent, before and after treatment, was performed in triplicate. The physico-chemical parameters were measured in accordance with the Standard Methods (APHA, 2005). A complete experimental design DEC 33 was proposed to estimate the best operating conditions of the treatment process, based on the variables initial pH of the reaction medium, concentration of Fe+3 ions and concentration of hydrogen peroxide, with the responces reduction of COD and decolorization of the effluent. These assays were performed in 240 min reaction and kept under stirring at about 150 rpm. A quadratic polynomial model was fitted to the experimental data obtained by the DEC 33 and submitted to ANOVA using the Statistica software and the free software Action. From the best results in the DEC 33, independent tests were performed to analyze the influence of the variables: initial pH of the reaction medium, concentration of Fe+3 ions, hydrogen peroxide concentration and the agitation of the reaction medium, operational temperature and the solution irradiationin 600 min kinectic. A UV-Vis spectrophotometer was used to scan 200-800 nm for the identification of the main absorption band of each dye. The determination of metals were performed by Total Reflection X-Ray Fluorescence (TXRF). The identification of the crystal phase sludge before and after the treatment was performed by X-ray diffraction (XRD). The identification of functional groups was made using the FTIR equipment, applying the ATR technique. The toxicity of the effluent after treatment, was evaluated by applying the ecotoxicity and phytotoxicity tests. The best photoreactor operating conditions were initial pH 2.8; 0.17 g L-1 of Fe3+, 8 g L-1 H2O2 and 240 min reaction, with reductions of 93% CODand 99% color. XRD analysis indicated the presence of sodium chloride before and after the effluent treatment. The FTIR analysis identified the appearance of a band at 1093 cm-1, after the adjustment of pH, suggesting the presence of carboxalate groups. For the bioindicator Artemia salina, there was no evidence of toxicity associated with the effluent after the treatment. For the bioindicator Lactuca sativathe effluent proved to be toxic after the treatment due to the presence of sodium chloride. The results showed that the photo-Fenton reaction induced by ferrioxalate was suitable for the treatment of the textile effluent used in this study.